Anticipatory action in communities hosting refugees and internally displaced persons: a synthesis report with case studies from Ethiopia, Jordan and Pakistan - Adam-Bradford, A.; Anagreh, A.; Dessalegn, Mengistu; Hafeez, Mohsin; Khalid, Sidra; Mekuria, Wolde; Melaku, Dagmawi; Schindler, A.; Singh, Radhika; Ruckstuhl, Sandra (International Water Management Institute (IWMI). CGIAR Initiative on Fragility, Conflict, and Migration, 2024)
UNHCR (2024a) reports that by June 2024 there were an estimated 122.6 million people around the world who have been forced to flee their homes. Among them were nearly 43.7 million refugees. This poses immense challenges for the humanitarian sector. These challenges are particularly acute in fragile states, such as Libya, Somalia, South Sudan and Syria, where civil war has pushed respective populations into extreme levels of vulnerability. Likewise, in the Occupied Palestinian Territories and Ukraine, ongoing wars have created impossible conditions for the humanitarian sector. Forced displacement from war, conflict and disasters is putting additional pressure on natural resources, such as food, land, and water systems (FLWSs) in host communities, in some cases leading to tensions between internally displaced persons (IDPs), refugees, and their hosts.